Autoimmune neutropenia of infancy. - Lyall, E. G. (1992)
AIM: Assessment of the clinical and haematological course of autoimmune neutropenia of infancy (ANI) in a defined childhood population in the south east of Scotland. METHODS: From January 1986 to February 1991 all children presenting with persistent neutropenia were examined serologically for evidence of antigranulocyte antibodies. The clinical course of those children found to have anti-granulocyte antibodies was then closely monitored. RESULTS: During the study period five children had serologically confirmed ANI, giving an annual incidence of approximately 1/100,000 in this population. All of these cases followed the classic benign course of the condition. The presenting illnesses were mild, often with superficial skin sepsis and the initial absolute neutrophil count (ANC) ranged from 0.00-0.87 x 10(9)/l. All have remained well with no serious infections. Two children attained a normal ANC after 14 and 24 months respectively, the others currently remain neutropenic. CONCLUSIONS: Autoimmune neutropenia of infancy is a condition which rests on a serological diagnosis. It follows a chronic benign course and all children eventually attain a normal ANC. The level of antigranulocyte antibody in the serum often begins to wane prior to improvement in the ANC and can give an indication of when recovery will begin to occur.